Sherlock Holmes e a Opção pela Conciliação : pistas para Ensino de Direito segundo a Experiência Brasileira - Malanovicz, Aline Vieira (2020)
Sherlock Holmes and the Conciliation Option: Law Teaching Clues according to the Brazilian Experience. --Abstract: Sir Arthur Conan Doyle's stories starring Sherlock Holmes are examples of texts full of cases of conflict with the law that can be the source of reflections on various institutes of criminal law, from the investigation itself, to forms of conflict resolution, such as the trial, imprisonment, alternative measures, and conciliation. The purpose of this research is to identify examples of reconciliation solutions in the Sherlock Holmes stories. The research method involved data collection in the television series "The Adventures of Sherlock Holmes"; schematic identification of how to resolve the conflict (using the categories Prison, Trial, Absolution, Death, Suicide, Wreck, Escape, Exile, Non-Crime, Stifled Case, Confession, Damage Repair, Conciliation); selection of stories categorized as having a conciliation solution; more detailed exploration of these stories; and later conference of the corresponding text excerpts in the Sherlockian canon. The results show that in at least three of Sherlock Holmes´ 60 stories, (The Noble Bachelor, The Three Students, and The Sussex Vampire tales) the Great Detective opts for a compromise solution to the conflict rather than taking the criminal to the British court. It follows that the Sherlock Holmes stories investigated here present situations of conflict with the law, which were resolved through conciliation. Like other stories in the so-called police literature, it is clear that these texts, while entertaining, have broad potential to raise reflections on the dynamics of criminal law.